Strategy for Nano‐Catalysis in a Fixed‐Bed System. (9th April 2014) - He, Jiating; Ji, Weijie; Yao, Lin; Wang, Yawen; Khezri, Bahareh; Webster, Richard D.; Chen, Hongyu
<x xml:space="preserve">Abstract</x> For industry applications of nano‐catalysts, the main bottlenecks are the low loading per unit support area and the slow flow rate through the support particles. By growing a dense Au nanowire forest on a loose network of glass fibers, continuous‐flow catalysis can be achieved with a processing rate about 100 times that of the best literature rate. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>